2019
DOI: 10.1016/j.compstruct.2019.111415
|View full text |Cite
|
Sign up to set email alerts
|

In-plane crashworthiness of re-entrant hierarchical honeycombs with negative Poisson’s ratio

Abstract: Both auxetic structures and hierarchical honeycombs are marked with lightweight and excellent mechanical properties. Here, we combine the characteristics of auxetic structures and hierarchical honeycombs, and propose two re-entrant hierarchical honeycombs constructed by replacing the cell walls of re-entrant honeycombs with regular hexagon substructure (RHH) and equilateral triangle substructure (RHT). The honeycombs are subjected to in-plane impact in order to investigate the crashworthiness by using the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(55 citation statements)
references
References 35 publications
(39 reference statements)
1
54
0
Order By: Relevance
“…A lot of effort has been put to analyze the static and dynamic energy absorption capabilities of auxetic structures, through both experimental and numerical methods. For example, Tan et al [22] parametrically studied the deformation modes and energy absorption capabilities of re-entrant hierarchical hexagonal honeycombs and demonstrated that both their proposed solutions exhibit an improved crushing performance. To further improve the energy absorption performance in impact, Wang et al [23] designed and studied a novel auxetic structure named re-entrant star-shaped honeycomb (RSH) and showed, through both experimental and numerical simulation, that RSH shows excellent impact resistance, compared with the classical re-entrant honeycomb (RH) with same cell wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of effort has been put to analyze the static and dynamic energy absorption capabilities of auxetic structures, through both experimental and numerical methods. For example, Tan et al [22] parametrically studied the deformation modes and energy absorption capabilities of re-entrant hierarchical hexagonal honeycombs and demonstrated that both their proposed solutions exhibit an improved crushing performance. To further improve the energy absorption performance in impact, Wang et al [23] designed and studied a novel auxetic structure named re-entrant star-shaped honeycomb (RSH) and showed, through both experimental and numerical simulation, that RSH shows excellent impact resistance, compared with the classical re-entrant honeycomb (RH) with same cell wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Li and coworkers combined the stacked Miura origami and rhombic honeycomb structure to develop new mechanical metamaterials with a two-stage programmable compressive strength [50]. The concept of this combination of different configurations to gain incredible performances has received considerable attention in many fields [51]. Alternatively, introducing additional microstructures to the mechanical metamaterial is another promising way to significantly improve the performance [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies on hierarchical honeycombs have added substructures such as squares, hexagons, and kagomes [ 23 , 24 , 25 , 26 , 27 , 28 ]. H. L. Tan et al added triangular subunits into concave hexagons and obtained excellent mechanical properties [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies on hierarchical honeycombs have added substructures such as squares, hexagons, and kagomes [24][25][26][27][28][29]. H. L. Tan et al added triangular subunits into concave hexagons and obtained excellent mechanical properties [30,31]. However, when these honeycomb structures [23][24][25][26][27][28][29] are subjected to quasi-static impact, the strain corresponding to the linear elastic zone is relatively large and cannot reach the platform zone quickly, therefore, the energy absorption effect is poor in the early stage.…”
Section: Introductionmentioning
confidence: 99%